Hand Hygiene Social Norms Among Healthcare Workers During Early COVID-19: Results of a Global Survey - Giorgia Gon; Aron Szekely; Aron Szekely; Hattie Lowe; Marco Tosi (Frontiers Media S.A., 2022)
Objectives: Poor hand hygiene among healthcare workers is an important driver of infectious disease transmission. Although social norms are considered a key determinant of hand hygiene behaviour, little is known about them among healthcare workers. This study describes hand hygiene social norms among health workers, assesses their predictors, and tests if social expectations increased during the early stages of COVID-19.Methods: We conducted a cross-sectional survey of healthcare workers from 77 countries (n = 1,233) from April to August 2020 assessing healthcare workers' hand hygiene social expectations, personal normative beliefs, punishment and reward, and demographic factors. Linear regressions and hierarchical linear modelling were used to analyse the responses.Results: We find high social expectations, personal beliefs, punishment, and rewards. Doctors tend to have lower social expectations than other occupation groups (e.g., nurses/midwives) and older respondents have higher social expectations. Social expectations increased during our survey, which may have been driven by COVID-19.Conclusion: Our findings suggest that hand hygiene social norms are strong among healthcare workers with variation across occupation and age; their strength increased during the COVID-19 pandemic. These have implications for behaviour change in healthcare environments that could leverage more norm-targeting interventions.